Macroeconomic and bank specific covariates of Non-Performing Loans (NPLs) in Pakistani Commercial Banks: panel data evidence / Bilal Mehmood, Zahid Irshad Younas, Nisar Ahmed. - Mehmood, Bilal; Younas, Zahid Irshad; Ahmed, Nisar (Universiti Teknologi Mara Selangor, 2013)
Non-performing loans has become an important part of commercial banking of a country. This paper empirically tests the macroeconomic and bank-specific covariates of non-performing loans for a panel of 13 commercial banks for period of 2003-2012. Using fixed effects with Driscoll and Kraay standard errors, the influence of macroeconomic and bank-specific covariates is found meaningful. Recommendations include the policy steps to complement the sound financial system with a healthy macroeconomic environment to reduce non-performing loans in commercial banks in Pakistan. Moreover, need is highlighted for a policy approach with emphasis on the apposite credit culture and lending policy designed with pertinent economic and financial factors.